Raman spectroscopic study of bioactive silica-based glasses: The role of the alkali/alkali earth ratio on the Non-Bridging Oxygen/Bridging Oxygen (NBO/BO) ratio. Issue 3 (2009) - Marsich Marsich, Lucia Lucia; Moimas Moimas, Loredana Loredana; Sergo Sergo, Valter Valter; Schmid Schmid, Chiara Chiara
Abstract : Raman spectra of bioactive glasses of the Na2 O–K2 O–MgO–CaO–B2 O3 –P2 O5 –SiO2 to be used in bone reconstruction systems have been collected from samples with three different concentrations of alkali and alkali earth elements. Compositions were chosen with a constant total amount of modifiers and formers, with only minor changes among the formers. The ratio of Non-Bridging Oxygens to Bridging Oxygens (NBO/BO) has been obtained from the Raman spectra and reported as a function of the alkali/alkali earth ratio, showing a linear increase. Dissolution tests indicate also a linear dependence of the amount of Na +, K + and Ca ++ ions leached in water on the alkali/alkali earth ratio. Consequently a calibration plot correlating the NBO/BO ratio with the amount of Na +, K + and Ca ++ ions leached in water has been obtained, thus demonstrating the sensitivity of the method, given that the changes from one glass composition to the other are of the order of some points in percentage among the glass modifiers.